Risk factors for suicide in depression in Finland: first‐hospitalized patients followed up to 24 years. (12th December 2018) - Aaltonen, K. I.; Isometsä, E.; Sund, R.; Pirkola, S.
Abstract : Objective: To examine longitudinally risk factors for suicide in depression, and gender differences in risk factors and suicide methods. Method: We linked data from (i) The Finnish Hospital Discharge Register, (ii) the Census Register of Statistics Finland, and (iii) Statistics Finland's register on causes of deaths. All 56 826 first‐hospitalized patients (25 188 men, 31 638 women) in Finland in 1991–2011 with a principal diagnosis of depressive disorder were followed up until death (2587 suicides) or end of the year 2014 (maximum 24 years). Results: Clinical characteristics (severe depression adjusted hazard ratio [AHR] 1.19 [95% CI 1.08–1.30]; psychotic depression AHR 1.45 [1.30–1.62]; and comorbid alcohol dependence AHR 1.26 [1.13–1.41]), male gender (AHR 2.07 [1.91–2.24]), higher socioeconomic status and living alone at first hospitalization were long‐term predictors of suicide deaths. Highest risk was associated with previous suicide attempts (cumulative probability 15.4% [13.7–17.3%] in men, 8.5% [7.3–9.7%] in women). Gender differences in risk factors were modest, but in lethal methods prominent. Conclusion: Sociodemographic and clinical characteristics at first hospitalization predict suicide in the long term. Inpatients with previous suicide attempts constitute a high‐risk group. Despite some gender differences in risk factors, those in lethal methods may better explain gender disparity in risk.